Pengaruh Penyuluhan HIV/AIDS Terhadap Persepsi Masyarakat di Desa Laburunci Kabupaten Buton - Sufrianto; Supodo, Timbul; Kamalia; Abadi, Ellyani (Metta : Jurnal Ilmu Multidisiplin, 2022)
HIV/AIDS is a global disease with an increasing number of events each year, especially in Laburunci Village, Buton Regency, Southeast Sulawesi, where a part of the population is migrants, so that they are at risk of HIV/AIDS. The public perception of HIV/AIDS in Laburunci village, which considers that the disease is a curse and is a disgrace for the suffering family. Efforts to improve public perception can be done by providing health education in the form of counseling with lecture methods and leaflet media which are still rarely performed in communities in Laburunci Village. Therefore, this study aims to determine the effect of HIV/AIDS counseling on community perception in Laburunci village, Buton Regency. This type of research is an experimental research design with one group pretest-posttest. This research was conducted on 4 September-4 October 2019 in Laburunci Village. Sampling using simple random sampling technique that is simple random sampling of 30 people. The results showed that the average perception score before counseling was 18.703 and increased to 25.37 after counseling. Wilcoxon sign rank test statistical test results obtained p value of 0,000 <α (0.05). The conclusion is the influence of HIV/AIDS counseling on community perception in Laburunci Village, Buton Regency.